Pocketbook as Teaching Material in Increasing Foreign Speakers’ Indonesian Vocabulary Based Upon Cultural Content - Uki Hares Yulianti; Ida Zulaeha; Rustono Rustono; Yusro Edy Nugroho (International Conference on Science, Education, and Technology, 2023)
Today pocketbooks as a media to learn Indonesian language have started to be developed by various institutions which enrol the program in Teaching Indonesian Language for Foreign Speakers (BIPA). Pocketbook is used as an alternative teaching material to increase foreign students’ Indonesian vocabulary not only that, but also aims to introduce Indonesian culture. Indonesian cultural values must be understood by foreign speakers, thus they can adapt well with Indonesian society. The method that is used by the researcher is experimental study. The data is gathered by conducting Indonesian language vocabulary tests before and after the students learn the pocketbook. The data is analyzed by implementing an independence exam. The research shows that after the students learned from the Pocketbook containing cultural content, they have shown significant ability in mastering Indonesian vocabulary compared to those with controlled groups. Besides, the foreign students also started to recognize cultural values around the environment they live in. For example, the foreign students who are studying in Jenderal Soedirman University, have shown the attitude that they have understood cultural customs and values in Banyumas Regency. It shows that the usage of Indonesian Language Pocketbook has proven to be effective in increasing foreign students' Indonesian vocabulary and as a media to understand cultural customs and values which exist in Indonesia. Therefore, an Indonesian Language Pocketbook which contains cultural content can be an effective alternative that supports the learning process of Indonesian Language for Foreign Speakers. This finding hopefully can help to increase the program efficiency to the learning process of Indonesian Language for Foreign Speakers (BIPA) in Indonesia.